DEVELOPING ACTIVE LEARNING ACTIVITIES ABOUT INVENTIONS TO ENHANCE THE ACADEMIC ACHIEVEMENT AND THE CREATIVE THINKING ABILITIES OF MATHAYOM 1 STUDENTS - Wongkamjan, Jitraporn; karin, yuanjai (Journal for Developing the Social and Community, 2024)
This research has the following objectives: 1) To develop active learning activities of Mathayom 1 students to be effective according to the 75/75 criteria. 2) To compare creative thinking abilities through active learning for Mathayom 1 students with the 75% criterion. 3) To compare the academic achievement of Mathayom 1 students before and after receiving active learning activities. The sample group used in this research were Mathayom 1 students at Nong Phok Wittayalai School, Nong Phok District, Roi Et Province, Roi Et Secondary Educational Service Area Office, in the 2nd semester of the 2023 academic year. There was 1 classroom with 35 students, which were obtained by Cluster Random Sampling.The research tools included an active learning activity plan, a creativity test, and an academic achievement test. Statistics used in data analysis include mean, standard deviation, percentage, and t-test. The results of the research found that 1) the efficiency of the plan for organizing active learning activities on crafts to enhance the creative thinking ability of Mathayom 1 students had E1/E2 efficiency higher than the efficiency criteria set at 75/75. 2) Students who received active learning activities had an average of creative thinking after studying higher than the 75% threshold with a statistical significance of .05 and 3) The academic achievement of Mathayom 1 students who received active learning activities had a significantly higher mean academic achievement after studying than before studying at the .05 level.